2018
DOI: 10.1194/jlr.m078162
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins D2 and E2 have opposite effects on alveolar macrophages infected with Histoplasma capsulatum

Abstract: Prostaglandin E (PGE) suppresses macrophage effector mechanisms; however, little is known about the function of PGD in infected alveolar macrophages (AMs). Using serum-opsonized (Ops-) in vitro, we demonstrated that AMs produced PGE and PGD in a time-dependent manner, with PGE levels exceeding those of PGD by 48 h postinfection. Comparison of the effects of both exogenous PGs on AMs revealed that PGD increased phagocytosis and killing through the chemoattractant receptor-homologous molecule expressed on Th2 ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 53 publications
1
26
0
1
Order By: Relevance
“…Despite the increased number of macrophages, we observed accumulation of degenerated fibers in T14 L ‐ pgds −/− nerves. Notably, we demonstrate that L‐PGDS promotes macrophage activity similarly to previous works showing that treatment of infected alveolar macrophages with PGD 2 increases macrophage phagocytosis (Pereira et al, ). Thus, although in L ‐ pgds −/− nerves macrophages are less active and myelin clearance is delayed, their accumulation at T14 likely compensates for their reduced phagocytic activity.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the increased number of macrophages, we observed accumulation of degenerated fibers in T14 L ‐ pgds −/− nerves. Notably, we demonstrate that L‐PGDS promotes macrophage activity similarly to previous works showing that treatment of infected alveolar macrophages with PGD 2 increases macrophage phagocytosis (Pereira et al, ). Thus, although in L ‐ pgds −/− nerves macrophages are less active and myelin clearance is delayed, their accumulation at T14 likely compensates for their reduced phagocytic activity.…”
Section: Discussionsupporting
confidence: 90%
“…That might be explained by the fact that eicosanoid encapsulation preserves the biological activity of lipid mediators by preventing their degradation (9). In fact, PGE 2 have been effectively encapsulated in PLGA with no loss of biological activity, because lactic/glycolic acid polymers show high encapsulation efficiency and adequate stability (10). A similar method for loading of PGE 2 showed that peak levels were reached in the first 4 h, but it could also be released continuously over longer periods (11).…”
Section: Discussionmentioning
confidence: 99%
“…One shortcoming is that PGE 2 shows a half-life relatively short. Therefore to preserve its biological activities and protect the mediator from degradation, loading of lipid mediators in microspheres has been used as a pharmacological strategy (9,10). However, the role of lipid mediator, loaded in microspheres or are not, in dental pulp cell differentiation is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid mediators derived from arachidonic acid are widely studied in inflammation and inflammatory cell differentiation (Secatto et al, 2014;Zoccal et al, 2016;Prado et al, 2017;Pereira et al, 2018). However, the role of these mediators in osteoclast precursor cell populations present at the inflammation site is poorly understood.…”
Section: Introductionmentioning
confidence: 99%